Mindaugas Navakas’s Radical Vilnius in the Context of Central and Eastern European Utopian Architecture Projects of the Second Half of the Twentieth Century (Relevant Tomorrow / Aktualu rytoj, 2023)
In Central and Eastern Europe, during the 1960s–1980s, artists’ efforts to oppose and criticize the architecture promoted by the socialist regime and to create an alternative to it became increasingly evident. The article investigates Mindaugas Navakas’s (b. 1952) photomontages of radical Vilnius in the context of critical utopian architecture projects of the second half of the twentieth century in Central and Eastern Europe. It introduces a new source that has not been explored in either Lithuanian or international studies of conceptual architecture, Navakas’s Vilnius Notebook (1981–1985): twelve utopian proposals for various areas of Vilnius—from the city center to the Gariūnai district. Comparison with Czech, Slovak, Polish, Hungarian, Latvian, and Estonian architectural utopias shows the kinship of Navakas’s projects with the architectural ideas of Central and Eastern European artists of the same period. The analysis further reveals that Navakas’s and his contemporaries’ experimental urban projects elevated the late twentieth-century architecture of Central and Eastern Europe to a new conceptual level, transcending the immediate limits of perspective and reality.
Keywords: utopia; conceptual architecture; Mindaugas Navakas; Alex Mlynárčík; Milan Knížák; Jiří Kovanda; László Rajk; Leonhard Lapin; Vilnius; Central and Eastern Europe